Directive Speech Acts in the Animated Sci-Fi Film “Next Gen”: A Pragmatic Analysis - I Kadek Adi Wisnu Pramana Putra; I Gusti Ayu Agung Sintha Satwika (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study investigates directive speech acts in the animated science fiction film Next Gen (2018) using the theoretical framework of Searle and Vanderveken (1985). The research aims to identify, categorize, and describe the types of directive speech acts performed by the characters, with particular attention to how language shapes human–robot interaction. The data were obtained from the film transcript, transcribed from Netflix subtitles, and analyzed through a qualitative descriptive approach. A total of 56 utterances containing directive speech acts were identified and classified into eight types: command, forbid, ask, suggest, request, urge, order, and permit, with command emerging as the most dominant (26 occurrences). The findings reveal that communication in Next Gen is strongly influenced by power dynamics and authority, while also reflecting interpersonal dimensions through requests, suggestions, and permissions, especially in relation to trust, care, and cooperation. The significance of this study lies in demonstrating how human–robot interaction can be understood through language use, offering insights into both pragmatic theory and media discourse analysis. By highlighting how directive speech acts construct relationships between humans and robots, the study contributes to broader discussions of language, interaction, and representation in science fiction narratives.